Aesthetic Style: How Material Objects Structure an Institutional Field. (March 2022) - Adler, Gary J.; DellaPosta, Daniel; Lankes, Jane
How does material culture matter for institutions? Material objects are increasingly prominent in sociological research, but current studies offer limited insight for how material objects matter to institutional processes. We build on sociological insights to theorize aesthetic style, a shared pattern of material object presence and usage among a cluster of organizations in an institutional field. We use formal relational methods and a survey of material objects from religious congregations to uncover the aesthetic styles that are part of the "logics of god" in the United States' Christian religious field. We argue aesthetic styles help structure an institutional field by spanning objects' meanings across space and time, stabilizing objects' authority, and demarcating symbolic boundaries. Our research provides a conceptual tool for understanding how objects bridge the material and symbolic dimensions of institutions and a methodological example for examining the meaning of objects across numerous organizations in an institutional field.